Semiconductor Based Power Devices for Sustainable Energy - Shiyanbola, Joseph (Lembaga Yasin AlSys, 2025)
This study explores the potential of wide bandgap (WBG) devices, specifically Gallium Nitride (GaN) and Silicon Carbide (SiC), in enhancing the performance and efficiency of modern energy systems, with a focus on renewable energy applications and electric vehicle (EV) technologies. WBG devices offer superior electrical properties compared to conventional silicon based components, particularly in high temperature and high frequency operations. Despite their advantages, the high cost of GaN and SiC, thermal management challenges, and long term reliability under real world conditions remain significant barriers to their widespread adoption. This paper reviews the current state of WBG device technology and identifies key areas for future research, including cost reduction strategies, thermal management innovations, and improvements in long term reliability. Furthermore, the integration of these devices into solar inverters and electric vehicle chargers and powertrains is examined, highlighting their potential to improve efficiency, reduce system size and weight, and lower costs. The findings suggest that continued research into WBG devices could significantly contribute to the development of more efficient, cost effective, and sustainable energy systems.